Sytuacja autorytarna i rządy prawa. Socjologiczno-prawne wyjaśnienia kryzysu konstytucyjnego - Pichlak, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The paper surveys the existing explanations of the current Polish constitutional crisis. For that sake the paper adopts a socio-legal perspective and introduces the concept of authoritarian situation, interpreted as a complex of social conditions which enable and/or facilitate the authoritarian form of government. As the examined studies prove, such an authoritarian situation has made a constitutional crisis in Poland possible. The paper discusses the explanations which concentrate on various factors conditioning the crisis, such as: class antagonism, the conﬂict of ideologies, the general legal culture of Polish society, professional legal culture, binding legal rules, and the condition of legal institutions (of law-making, law-applying, and constitutional politics). This discussion allows a conclusion that the causes of the constitutional crisis are multiple and much deeper than the current political conﬂict.
Keywords: constitutional crisis; authoritarianism; authoritarian situation; social authoritarianism; political authoritarianism; constitutionalism; societal constitutionalism; rule of law